The Łódź School of Economics 2014–2024: Institute of Economics - Burchard-Dziubińska, Małgorzata; Dorożyński, Tomasz; Dzionek-Kozłowska, Joanna; Gajewski, Paweł; Kowalski, Kamil; Kozłowski, Maciej; Kuna-Marszałek, Anetta; Legiędź, Tomasz; Majchrowska, Aleksandra; Skorupińska-Cieślak, Katarzyna; Świerkocki, Janusz; Wyszkowska-Kuna, Joanna (Scientific Schools and Research Directions at the Faculty of Economics and Sociology, University of Łódź: The Present and the Future, 2025)
The chapter presents the history and current development of the Institute of Economics at the Faculty of Economics and Sociology, University of Łódź. The authors discuss research and teaching traditions, focusing especially on the last decade.